MODERN DEFINITIONS AND PRINCIPLES OF INTENSIVE CARE OF SEPSIS IN CHILDREN - A. U. Lekmanov; P. I. Mironov; V. A. Rudnov; V. V. Kulabukhov (Вестник анестезиологии и реаниматологии)
The review is devoted to one of the most critical issues of modern intensive care – the diagnostics of sepsis in children. The article describes the modern definition of sepsis and presents the review of the recent publications devoted to pediatric sepsis. It speculates on the benefits and drawbacks of Sepsis-3 recommendations for pediatric intensive care. The special emphasis is put on the early detection and assessment of organ failure severity in the children with an infection using special scores of qSOFA or PELOD-2.